English World 8 B1 Student's book - Bowen, Mary; Hocking, Liz; Wren, wendy (Oxford Macmillan, 2012)
The Student's Book contains twelve units. Each requires eight teaching sessions and is designed to be taught over a two-week period. The key skills of reading, writing, speaking and listening are consistently covered throughout the course and are underpinned by the firm foundation of the grammar syllabus. These elements are clearly presented in the book so that teachers have a clear objective for every lesson. KEY FEATURES - Welcome unit to revises the basic language needed to begin the course - Stories, dialogues, information texts, songs and poems to attract and motivate young learners
Languages
2
Keywords: English language